Early ecological trajectories of native woodlands established under Ireland’s Native Woodland Scheme - Kate Harrington; Fraser J.G. Mitchell; Jane C. Stout (Forest Ecology and Management, 2026)

From flowers to pollinators: Dietary exposure of honey bees, bumble bees and solitary bees to trace elements across European fields - Maciej Durkalec; Agnieszka Nawrocka; Petru Jitaru; Marie-Pierre Chauzat; Marion Laurent; Matthias Albrecht; Cecilia Costa; Pilar De la Rúa; Alexandra-Maria Klein; Marika Mänd; Simon G. Potts; Maj Rundlöf; et al. (Journal of Hazardous Materials, 2026)

Aligning nature sustainability reporting requirements across national, business and farm scale: lessons from Ireland - Catherine A. Farrell; Cian White; Lars Hein; Carl Obst; Martha O'Hagan Luff; Orlaith Delargy; Jane C. Stout (Journal of Environmental Management, 2026)

Ecosystem accounting for biodiversity surrounding windfarms - Emma King; Jane C. Stout; Yvonne M. Buckley; Ian Donohue (Journal of Environmental Management, 2025)

Variation in the pollen diet of managed bee species across European agroecosystems - Clément Tourbez; Antoine Gekière; Irene Bottero; Marie-Pierre Chauzat; Elena Cini; Francesca Corvucci; Joachim R. de Miranda; Gennaro Di Prisco; Christophe Dominik; Francesca V. Grillenzoni; Simon Hodge; Tomasz Kiljanek; et al. (Agriculture, Ecosystems & Environment, 2025)

Pollen-Derived Fatty Acids and Amino Acids Mediate Variance in Pollinator Visitation - Anne F. Murray; Sara D. Leonhardt; Jane C. Stout; Fabian A. Ruedenauer; Maryse Vanderplanck; Laura Russo (Journal of Chemical Ecology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

A decision methodology for site-level ecosystem accounting - Courtney E. Gorman; Francesco Martini; Kathleen Conroy; Emma King; Reiss Mcleod; Carl Obst; Jane C. Stout; Ian Donohue; Yvonne M. Buckley (Journal of Environmental Management, 2024)

A blood test to monitor bee health across a European network of agricultural sites of different land-use by MALDI BeeTyping mass spectrometry - Dalel Askri; Mathilde Pottier; Karim Arafah; Sébastien N. Voisin; Simon Hodge; Jane C. Stout; Christophe Dominik; Oliver Schweiger; Giovanni Tamburini; Maria Helena Pereira-Peixoto; Alexandra-Maria Klein; Vicente Martínez López; et al. (Science of The Total Environment, 2024)

Novel indices reveal that pollinator exposure to pesticides varies across biological compartments and crop surroundings - Marion LAURENT; Stéphanie BOUGEARD; Lucile CARADEC; Florence GHESTEM; Matthias ALBRECHT; Mark J.F. BROWN; Joachim DE MIRANDA; Reet KARISE; Jessica KNAPP; José SERRANO; Simon G. POTTS; Maj RUNDLÖF; et al. (Science of The Total Environment, 2024)

Honey bees and bumble bees may be exposed to pesticides differently when foraging on agricultural areas - Elena Zioga; Blánaid White; Jane C. Stout (Science of The Total Environment, 2023)

Pesticide mixtures detected in crop and non-target wild plant pollen and nectar - Elena Zioga; Blánaid White; Jane C. Stout (Science of The Total Environment, 2023)

Responses in honeybee and bumblebee activity to changes in weather conditions - Arrian Karbassioon; Jon Yearlsey; Tara Dirilgen; Simon Hodge; Jane C. Stout; Dara A. Stanley (Oecologia, 2023)
Insect pollination, and in particular pollination by bees, is a highly valued ecosystem service that ensures plant reproduction and the production of high-quality crops. Bee activity is known to be influenced by the weather, and as the global climate continues to change, the flying frequency and foraging behaviour of bees may also change. To maximise the benefits of pollination in a changing world, we must first understand how current weather conditions influence the activity of different bee species. This is of particular interest in a country such as Ireland where inclement weather conditions are nominally sub-optimal for foraging. We observed honeybee ( Apis mellifera ) and buff-tailed bumblebee ( Bombus terrestris ) activity across a variety of weather conditions at seven apple orchards to determine how four weather variables (temperature, relative humidity, solar radiation, wind) influenced the flight activity of each species. Each orchard contained three honeybee and three bumblebee colonies, and so we were able to observe a colony of each species concurrently in the same weather conditions. Overall, honeybees were more sensitive to changes in weather than bumblebees and could be more predisposed to future changes in within-day weather conditions. Our results indicate bumblebees could compensate for low honeybee activity in inclement conditions, which supports the theory that pollinator diversity provides resilience. This may be particularly important in management of pollinators in crops that flower in the spring when weather is more variable, and to allow varied responses to global climate change.

Biocircularity: a Framework to Define Sustainable, Circular Bioeconomy - Nicholas M. Holden; Andrew M. Neill; Jane C. Stout; Derek O’Brien; Michael A. Morris (Circular Economy and Sustainability, 2023)
Bioeconomy is proposed as a solution to reduce reliance on fossil resources. However, bioeconomy is not always inherently circular and can mimic the conventional take, make, consume, dispose linear economic model. Agricultural systems will be relied on to provide food, materials, and energy, so unless action is taken, demand for land will inevitably exceed supply. Bioeconomy will have to embrace circularity to enable production of renewable feedstocks in terms of both biomass yield and maintaining essential natural capital. The concept of biocircularity is proposed as an integrated systems approach to the sustainable production of renewable biological materials focusing on extended use, maximum reuse, recycling, and design for degradation from polymers to monomers, while avoiding the “failure” of end of life and minimizing energy demand and waste. Challenges are discussed including sustainable production and consumption; quantifying externalities; decoupling economic growth from depletion; valuing natural ecosystems; design across scales; renewable energy provision; barriers to adoption; and integration with food systems. Biocircularity offers a theoretical basis and measures of success, for implementing sustainable circular bioeconomy.

Reconciling climate action with the need for biodiversity protection, restoration and rehabilitation - Courtney E. Gorman; Andrew Torsney; Aoibheann Gaughran; Caroline M. McKeon; Catherine A. Farrell; Cian White; Ian Donohue; Jane C. Stout; Yvonne M. Buckley (Science of The Total Environment, 2023)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Neonicotinoid residues in honey from urban and rural environments - Saorla Kavanagh; Michael Henry; Jane C. Stout; Blánaid White (Environmental Science and Pollution Research, 2021)

Contrasting impacts of highly invasive plant species on flower-visiting insect communities - Emily S. Davis; Ruth Kelly; Christine A. Maggs; Jane C. Stout (Biodiversity and Conservation, 2018)

Underestimating neonicotinoid exposure: how extent and magnitude may be affected by land-use change - Jesko Zimmermann; Jane C. Stout (Environmental Science and Pollution Research, 2016)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Pollinator sharing between mass-flowering oilseed rape and co-flowering wild plants: implications for wild plant pollination - Dara A. Stanley; Jane C. Stout (Plant Ecology, 2014)

Pollinators and pollination of oilseed rape crops (Brassica napus L.) in Ireland: ecological and economic incentives for pollinator conservation - Dara A. Stanley; Daryl Gunning; Jane C. Stout (Journal of Insect Conservation, 2013)

Effects of conspecific and heterospecific floral density on the pollination of two related rewarding orchids - Karl J. Duffy; Jane C. Stout (Plant Ecology, 2011)

A hierarchical framework for integrating invasibility experiments incorporating different factors and spatial scales - Ann Milbau; Jane C. Stout; Bente J. Graae; Ivan Nijs (Biological Invasions, 2009)

Inferring National and Regional Declines of Rare Orchid Species with Probabilistic Models - KARL J. DUFFY; NAOMI E. KINGSTON; BRENDAN A. SAYERS; DAVID L. ROBERTS; JANE C. STOUT (Conservation Biology, 2009)
Fragmentation of natural habitats can increase numbers of rare species. Conservation of rare species requires experts and resources, which may be lacking for many species. In the absence of regular surveys and expert knowledge, historical sighting records can provide data on the distribution of a species. Numerous models have been developed recently to make inferences regarding the threat status of a taxon on the basis of variation in trends of sightings over time. We applied 5 such models to national and regional (county) data on 3 red‐listed orchid species ( Cephalanthera longifolia , Hammarbya paludosa , and Pseudorchis albida ) and 1 species that has recently come to the attention of conservation authorities ( Neotinea maculata ) in the Republic of Ireland. In addition, we used an optimal linear estimate to calculate the time of extinction for each species overall and within each county. To account for bias in recording effort over time, we used rarefaction analysis. On the basis of sighting records, we inferred that these species are not threatened with extinction and, although there have been declines, there is no clear geographical pattern of decline in any species. Most counties where these orchid species occurred had a low number of sightings; hence, we were cautious in our interpretation of output from statistical models. We suggest the main drivers of decline in these species in Ireland are modification of habitats for increased agricultural production and lack of appropriate management. Our results show that the application of probabilistic models can be used even when sighting data are scarce, provided multiple models are used simultaneously and rarefaction is used to account for bias in recording effort among species over time. These models could be used frequently when making an initial conservation assessment of species in a region, particularly if there is a relatively constant recording rate and some knowledge of the underlying recording process. Regional‐scale analyses, such as ours, complement World Conservation Union criteria for assessment of the extinct category and are useful for highlighting areas of under recording and focusing conservation efforts of rare and endangered species.

Factors Associated with Alien Plants Transitioning from Casual, to Naturalized, to Invasive - ANN MILBAU; JANE C. STOUT (Conservation Biology, 2008)
To explain current plant invasions, or predict future ones, more knowledge on which factors increase the probability of alien species becoming naturalized and subsequently invasive is needed. We created a database of the alien plants in seminatural habitats in Ireland that included data on taxonomy, invasive status, invasion history, distribution, and biological and ecological plant characteristics. We used information from this database to determine the importance of these factors in increasing the ability of species to become naturalized and invasive. More specifically, we used two multiple logistic regressions to identify factors that distinguish naturalized from casual alien plant species and invasive from noninvasive, naturalized alien species. Clonal growth, moisture‐indicator value, nitrogen‐indicator value, native range, and date of first record affected (in order of decreasing importance) the probability of naturalization. Factors that distinguished invasive from noninvasive species were ornamental introduction, hermaphrodite flowers, pollination mode, being invasive elsewhere, onset of flowering season, moisture‐indicator value, native range, and date of first record. Incorporation of phylogenetic information had little influence on the results, suggesting that the capacity of alien species to naturalize and become invasive evolved largely independently in several phylogenetic lineages. Whereas some of the variables were important for both transitions, others were only important for naturalization or for invasion. This emphasizes the importance of studying different stages of the invasion process when looking for mechanisms of becoming a successful invasive plant, instead of simply comparing invasive with noninvasive alien species. Our results also suggest that a combination of species traits and other variables is likely to produce the most accurate prediction of invasions.

Pollination Ecology and Seed Production of Rhododendron Ponticum in Native and Exotic Habitats - Jane C. Stout; John A. N. Parnell; Juan Arroyo; Tasman P. Crowe (Biodiversity and Conservation, 2006)

Can alloethism in workers of the bumblebee, Bombus terrestris, be explained in terms of foraging efficiency? - Dave Goulson; James Peat; Jane C. Stout; James Tucker; Ben Darvill; Lara C. Derwent; William O.H. Hughes (Animal Behaviour, 2002)

Identity and Function of Scent Marks Deposited by Foraging Bumblebees - Dave Goulson; Jane C. Stout; John Langley; William O. H. Hughes (Journal of Chemical Ecology, 2000)

The influence of relative plant density and floral morphological complexity on the behaviour of bumblebees - Jane C. Stout; John A. Allen; Dave Goulson (Oecologia, 1998)

Repellent scent-marking of flowers by a guild of foraging bumblebees ( Bombus spp.) - Jane C. Stout; Dave Goulson; John A. Allen (Behavioral Ecology and Sociobiology, 1998)

Floral display size in comfrey, Symphytum officinale L. (Boraginaceae): relationships with visitation by three bumblebee species and subsequent seed set - Dave Goulson; Jane C. Stout; Sadie A. Hawson; John A. Allen (Oecologia, 1998)

Can flower constancy in nectaring butterflies be explained by Darwin's interference hypothesis? - D. Goulson; Jane C. Stout; Sadie A. Hawson (Oecologia, 1997)